A influência de aspectos da cultura gaúcha na constituição da identidade dos mato-grossenses filhos de migrantes sulistas : no C.T.G. "Estância da Amizade" - Hasselstrom, Agnéia Luciana Lopes de Siqueira (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation consists of a study conducted in conducted at the Center for Gaucho Traditions Hut of Friendship of Sinop (MT). The work focuses mainly on young people who were born in Mato Grosso, participate in C.T.G. Ranch of Friendship and have parents born in Southern Brazil. The objective is to understand the constitution of the identity of the people of Mato Grosso who are children of migrants from Southern Brazil who have settledin Sinop (MT) and the elements that characterize aspects the presence of he gaucho culture in this city. The research project developed consists of filming, photographs, semi-structured conversations and participation in activities underkaten by the C.T.G. Ranch Hut of Friendship for a period of four months. It is ethnography an ethnographic study supported by based on authors who have produced studies whose concepts provide greater understanding on provide a better understanding of the subject.
Keywords: Identidade; Cultura; Migrantes; Sociedade; Identity; Culture; Migrants; Society; ACCNPQ::Ciências Humanas::Sociologia